The borderland of civilizations as a research category in the sociology of borderland - Sadowski, Andrzej (Creativity Studies, 2009)
Current studies on the borderland territories suggest insufficiency of research tools, which, if applied, would improve the theoretical level of the conducted studies, particularly if that research would cover the borderlands of civilizations. Until now, the research on borderlands in Poland and elsewhere were dominated by the concepts of borderlands and trans‐borderness. In my opinion, to cover the full scope of social phenomena and processes, which appear on borderland and trans‐border territories, the new terms should be introduced: “borderlandness” together with the existing “borderland” and the “trans‐borderland” to complement with the “trans‐borderlandness”. In this paper I intend to present shortly the conception of the borderland applied in my research and, on this basis, I try to develop the concept of borderlandness as well as to stress its utility in the studies of borderlands, including the borders of civilizations.Civilizacijų paribys kaip tyrimo kategorija paribio sociologijojeSantrauka. Dabartinese paribio teritoriju studijose nepakanka tyrimo priemoniu, kurios galetu pagerinti teorine vykdomu tyrimu kokybe, ypač tokiu atveju, jei jie apimtu ir civilizaciju paribius. Iki šiol paribio tyrimuose Lenkijoje ir kitur vyravo paribio ir užribio konceptai. Pasak autoriaus, siekiant apimti socialiniu fenomenu ir procesu, vykstančiu paribio ir užribio teritorijose, visuma, dera pasitelkti naujas savokas. Jau vartojama savoka “paribys” papildytina savoka “paribiškumas”, o “užribis” ‐ “už‐ribiškumas”. Straipsnyje siekiama pristatyti paribio koncepcija, kuria naudojant siekiama pletoti paribiškumo samprata it pabrežti jos naudinguma paribio studiju, apimančiu ir civilizaciju ribas, atžvilgiu.Reikšminiai žodžiai: civilizacijų paribys, paribiškumas, paribio sociologija, tapatumas, užribiškumas.First Published Online: 14 Oct 2010